Treatment of Mycobacterium marinum with lymecycline: new therapeutic alternative? - Maria Gertrudes Fernandes Pereira Neugebauer; Samuel Antônio Neugebauer; Hiram Larangeira Almeida Junior; Laís Marques Mota (Sociedade Brasileira de Dermatologia, 2015)
Skin infections by Mycobacterium marinum are quite rare in our environment and, therefore, little studied. The majority of the lesions appear three weeks after traumas in aquariums, beaches and fish tanks. Lymph node drainage and systematization of the disease are rare and most lesions disappear in about three years. This case aims to show the effectiveness of the treatment used (lymecycline 150 mg/orally/day). This medication may be a new therapeutic option for the treatment of Mycobacterium marinum.